The Role Of Teachers In Encouraging Social Interaction Of Early Childhood In Islahul Ummah Kindergarten In The 2025 Academic Year - Alfiani, Dewi; Habiburrahman, Lalu; Eliyana, Eliyana (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Abstrak. This study aims to examine the strategies implemented by teachers in promoting social interaction among early childhood students, as well as the supporting and inhibiting factors in its implementation. The research was conducted at TK Islahul Ummah, Dusun Cupek, using a descriptive qualitative method. Data were collected through interviews, observations, and documentation.The findings indicate that teachers play a significant role as facilitators in creating a supportive and friendly learning environment. The strategies applied include the habituation of positive behaviors such as greeting others, cooperating, sharing, as well as conducting communal meals and joint clean-up activities. Teachers also serve as role models by demonstrating appropriate social behavior.Moreover, regular group activities have proven effective in developing children's social skills.Inhibiting factors include shy personalities, low self-confidence, limited vocabulary, and unsupportive environments. On the other hand, supporting factors include a safe school environment, friendly teacher attitudes, peer involvement, and parental support through parenting activities and school-home collaboration. Consistent habituation practices can shape children's social character from an early age.